Peran Pramuka Dalam Pembentukan Akhlak di Yp Al-Manar Hamparan Perak Medan - Arlina Arlina; Setia Ningsih; Anisa Fadillah; Jekson Parulian Harahap; Azaman Andra; M. Fauzi Rifqi; Leli Suharti (Peneliti.net, 2023)
Scouting activities have many benefits for students, one of which is for students at the Al-Manar Medan educational foundation. The purpose of this research is to find out and analyze the scouting activities in the Al-Manar educational foundation. The results of the study stated that scouting activities at the Al-Manar educational foundation provided many benefits, namely making students more disciplined, responsible, thinking creatively, and forming better morals. This is in line with Al-Ghazali's statement which states that the importance of moral education for students in schools.